PERILAKU PENGGUNA TIKTOK DALAM INTERAKSI LAWAN JENIS PERSPEKTIF AL-QURAN (KAJIAN QS. AL-AHZAB AYAT 32, 33, DAN 59) - Tulus Musthofa; Wanda Saputri Machmud (university Of islam, 2022)
Negative characters have been displayed by the Indonesian people under the pretext of being right to do including Muslim women who began to show their expertise in swaying to the audience through the Tik Tok application, this is certainly far from the Muslimah character contained in the Qur'an, especially QS. AL-Ahzab verses 32, 33, and 59. So as to invite the creation of interaction of the opposite sex that should not be. This research is a literature study or library research conducted through review and analysis of data relevant to books, e-books, journals, and other literature as data sources. The results of the study are that the use of Tik Tok applications without purpose and just follow the trend so that it always looks current has a less good and detrimental impact. The impact of the dance causes Muslimah aurat to be seen easily, especially curves, encrusted, to invite slander that can harm themselves. While men must always keep their views in order to analyze the emergence of interactions that should not be done between the opposite sex. To stay away from these things as Muslims need to understand the values contained in the teachings of Islam.